2015
DOI: 10.1073/pnas.1501659112
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cooperative bicarbonate uptake into chloroplast stroma in the green alga Chlamydomonas reinhardtii

Abstract: SignificanceThe entry of inorganic carbon (Ci; CO2 and HCO3–) into cells involves many biological processes in both animals and plants, and aquaporins as well as bicarbonate transporters play roles in Ci transport. Although transporting external HCO3– into the stroma through the chloroplast envelope is one of the rate-limiting factors for aquatic photosynthetic organisms, specific molecular components in this process have not yet been identified experimentally. Molecular identification of proteins essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 35 publications
1
109
0
Order By: Relevance
“…Because it was reported that CEF activity increases in LC conditions possibly for increased ATP demand for ABC-type bicarbonate transporter HLA3 in CCM (12,28) and that CAS is associated with the CEF complex formation in anaerobic conditions (26), it was possible that CAS-dependent CEF might contribute to CCM. However, CEF activity was not affected by the lack of CAS protein in the LC conditions at 120 μmol photons·m -2 ·s -1 that we examined ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because it was reported that CEF activity increases in LC conditions possibly for increased ATP demand for ABC-type bicarbonate transporter HLA3 in CCM (12,28) and that CAS is associated with the CEF complex formation in anaerobic conditions (26), it was possible that CAS-dependent CEF might contribute to CCM. However, CEF activity was not affected by the lack of CAS protein in the LC conditions at 120 μmol photons·m -2 ·s -1 that we examined ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of those genes regulated by CAS, HLA3 and LCIA, whose accumulation was decreased in H82 cells (Fig. 1D), are involved in HCO − 3 uptake for operation of the CCM (11)(12)(13)(14). However, simultaneous expression of HLA3 and LCIA could only partially rescue the decreased Ci affinity of H82 cells (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations